2016
DOI: 10.1038/srep29412
|View full text |Cite
|
Sign up to set email alerts
|

A threshold of endogenous stress is required to engage cellular response to protect against mutagenesis

Abstract: Endogenous stress represents a major source of genome instability, but is in essence difficult to apprehend. Incorporation of labeled radionuclides into DNA constitutes a tractable model to analyze cellular responses to endogenous attacks. Here we show that incorporation of [3H]thymidine into CHO cells generates oxidative-induced mutagenesis, but, with a peak at low doses. Proteomic analysis showed that the cellular response differs between low and high levels of endogenous stress. In particular, these results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
(44 reference statements)
1
7
0
Order By: Relevance
“…Although they are continuously exposed to such chronic low-level endogenous stresses, cells still proliferate and replicate their genome, suggesting that the DDR is not or not fully activated. Thus, this implies that a stress threshold is needed to be reached to fully activate the DDR, as previously proposed (Saintigny et al, 2016;Wilhelm et al, 2014Wilhelm et al, , 2016, and, as a corollary, that cells either do not respond to low-level stresses, or have developed specific alternative responses.…”
Section: Introductionsupporting
confidence: 59%
“…Although they are continuously exposed to such chronic low-level endogenous stresses, cells still proliferate and replicate their genome, suggesting that the DDR is not or not fully activated. Thus, this implies that a stress threshold is needed to be reached to fully activate the DDR, as previously proposed (Saintigny et al, 2016;Wilhelm et al, 2014Wilhelm et al, , 2016, and, as a corollary, that cells either do not respond to low-level stresses, or have developed specific alternative responses.…”
Section: Introductionsupporting
confidence: 59%
“…Gel spots 2D were manually cut and prepared, as previously described [ 38 ]. The LC-MS/MS experiments were performed using a U3000 NCS nano-high-performance liquid chromatography (Thermo Fisher Scientific Inc, Waltham, MA, USA) system and a Q-Exactive Plus Orbitrap mass spectrometer.…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies have revealed that a threshold level of genotoxic stress must be reached to trigger the DNA damage surveillance network [ 5 ]. This response is initiated by rapid stabilization of p53, its nuclear accumulation, and activation of its transcriptional and biological functions [ 24 ].…”
Section: Biological Outputs Orchestrated By Wild-type P53mentioning
confidence: 99%
“…Constitutively available DNA repair processes deal with low levels of genomic injury and assist in ameliorating the detrimental effects of such agents. An increase in DNA damage above a threshold level activates the DNA damage surveillance network, which involves multiple signaling pathways that protect against genomic instability and restrict aberrant cell growth in response to genotoxic stress [ 5 ]. The wild-type p53 tumor suppressor functions at the hub of this network [ 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%